PENGEMBANGAN INSTRUMEN PENILAIAN PSIKOMOTOR TARI KREASI SISWA DI SMP BERBASIS IT - Shara Marsita Mirdamiwati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2016)
This research was conducted using the research approach development (Research and Developmen) that steps are adapted from the spiral model. Instrument performance assessment (performance assessment) developed consisting of: (1) item task (task), (2) instructions for use, (3) an assessment rubric, (4) the observation sheet, and (5) guidelines for the interpretation of the results. Developing indicators psychomotor assessment instrument creation dance students performed with reference to the learning curriculum of dance class VII junior high school (SMP). Especially on basic competence (KD): (1) create a dance based on the pattern of the floor, and (2) to show the results of a dance piece based on the pattern of the floor. To assess the competence of the students in making the creation dance floor pattern used by performance assessment techniques with engineering practice test assignment feature dance creations based on the pattern of the floor. Based on the results of experiments performed at the stage of implementation of the model shows that, technically speaking psychomotor assessment model creation dance students developed IT-based can be applied properly. Based on the analysis of reliability test performed using inter-class correlation coefficient analysis (intraclass correlation coefficients / ICC) type definition consistency and type of absolute agreement definition shows also that the assessment instruments developed have met the established criteria.Keywords: assessment , psychomotor , dance creations